Variação espacial e temporal de uma taxocenose de caprelídeos (Crustacea: Amphipoda) em um ecossistema subtropical sujeito à poluição por hidrocarbonetos de petróleo - Silva, Danilo Balthazar (2010)
The petroleum demand, as so as the commerce of its derivates, has caused the introduction of these compounds in marine ecosystems. The transportation and the extraction of petroleum cause severe accidents, impacting coastal ecosystems through a lot of ways. Sargassum beds are very abundant and important to the maintenance of ecological processes in coastal regions. In Sargassum beds the infraorder Amphipoda is one of the most abundant taxonomic groups. Some amphipods species are considered important bioindicators of petrogenic pollution. The Amphipoda Caprellidae shows a high species diversity, and some species are considered strong bioindicators of anthropological impacts. Thus, it can be supposed that, given their potential as bioindicators, caprellids significantly respond to an oil pollutants gradient, as so as others amphipods. The São Sebastião Channel is located at the Brazilian southeastern coast. Oil vessels accidents are among the anthropological impacts in that area. The present study has two chapters. The first one brings evidences of caprellids taxocoenosis structure in a gradient of oil pollutants. The second describes a pattern of temporal variation of caprellids trophic groups. The results suggest that petrogenic pollutants affect caprellids species richness and evenness on the studied scales. A significant pattern of temporal variation was observed in the density of detritivores and omnivores. The results indicate a seasonal segregation in the density of the two groups.